تحليل جغرافي لاستعمالات الأرض الزراعية للمحاصيل الحقلية في ناحية الشحيمية للموسم الزراعي (2017- 2018) - مسير لفتة الزاملي, شاكر; جابر عفلوك القريشي, عماد (Journal of College of Education, 2020)
The research aims to reveal the geographical analysis of agricultural land uses in the Shuhaimia area as well as explaining the reasons that result from the nature of the agricultural process in these crops in order to optimize the investment of agricultural land according to the natural and human resources available within the study area. The prominent findings show that there are five crops that are cultivated which are  (Wheat, barley, yellow corn, cattle, millet) are grown in wide area (95371) dunums with a quantity of (86861.75) tons per year and are located on different areas during agricultural districts.